Hospital-Acquired COVID-19: Case Discussions of Two Patients Treated at a Level I Trauma Center - Ryan M. Desrochers; Jonathan D. Gates; Daniel Ricaurte; Jane J. Keating (Case Reports in Surgery)
The community spread of COVID-19 is well known and has been rigorously studied since the onset of the pandemic; however, little is known about the risk of transmission to hospitalized patients. Many practices have been adopted by healthcare facilities to protect patients and staff by attempting to mitigate internal spread of the disease; however, these practices are highly variable among institutions, and it is difficult to identify which interventions are both practical and impactful. Our institution, for example, adopted the most rigorous infection control methods in an effort to keep patients and staff as safe as possible throughout the pandemic. This case report details the hospital courses of two trauma patients, both of whom tested negative for the COVID-19 virus multiple times prior to producing positive tests late in their hospital courses. The two patients share many common features including history of psychiatric illness, significant injuries, ICU stays, one-to-one observers, multiple consulting services, and a prolonged hospital course prior to discharge to a rehabilitation facility. Analysis of these hospital courses can help provide a better understanding of potential risk factors for acquisition of a nosocomial COVID-19 infection and insight into which measures may be most effective in preventing future occurrences. This is important to consider not only for COVID-19 but also for future novel infectious diseases.